Restoration of miR-340 controls pancreatic cancer cell CD47 expression to promote macrophage phagocytosis and enhance antitumor immunity. Issue 1 (4th June 2020) - Xi, Qing; Zhang, Jieyou; Yang, Guangze; Zhang, Lijuan; Chen, Ying; Wang, Chengzhi; Zhang, Zimu; Guo, Xiangdong; Zhao, Jingyi; Xue, Zhenyi; Li, Yan; Zhang, Qi; et al.
Abstract : Background: Immune checkpoint blockade has emerged as a potential cancer immunotherapy. The "don't eat me" signal CD47 in cancer cells binds signal regulatory protein-α on macrophages and prevents their phagocytosis. The role of miR-340 in pancreatic ductal adenocarcinoma (PDAC), especially in tumor immunity, has not been explored. Here, we examined the clinical and biological relevance of miR-340 and the molecular pathways regulated by miR-340 in PDAC. Methods: CD47 and miR-340 expression and the relationship with cancer patient survival were analyzed by bioinformatics. The mechanism of miR-340 action was explored through bioinformatics, luciferase reporter, qRT-PCR and western blot analyses. The effects of miR-340 on cancer cells were analyzed in terms of apoptosis, proliferation, migration and phagocytosis by macrophages. In vivo tumorigenesis was studied in orthotopic and subcutaneous models, and immune cells from the peripheral and tumor immune microenvironments were analyzed by flow cytometry. Depletion of macrophages was used to verify the role of macrophages in impacting the function of miR-340 in tumor progression. Results: miR-340 directly regulates and inversely correlates with CD47, and it predicts patient survival in PDAC. The restoration of miR-340 expression in pancreatic cancer cells was sufficient to downregulate CD47 and promote phagocytosis of macrophages, further inhibiting tumor growth. The overexpression of miR-340 promoted macrophages to become M1-like phenotype polarized in peripheral and tumor immune microenvironments and increased T cells, especially CD8 + T cells, contributing to the antitumor effect of miR-340. Conclusions: miR-340 is a key regulator of phagocytosis and antitumor immunity, and it could offer a new opportunity for immunotherapy for PDAC.